The Communication Channels and the Innovation Perception on The Adoption of E-Commerce in Micro, Small Medium Enterprises (MSMEs) - Maharani Imran (Yayasan Ilomata, 2023)
The number of MSMEs products sold through e-commerce in Indonesia is considered insignificant, therefore, proper strategies are needed to increase the adoption of e-commerce. The purpose of this study is to explore the communication channels and the innovation perceptions on e-commerce adoption in MSMEs. A qualitative approach and a case study method are used. The analysis consists of four medical device retailers, with observation and in-depth interviews as the data collection, and an implementation of a thematic data analysis technique. The communication channels that influence the adoption of e-commerce innovation technology are mass media, interpersonal communication, and interaction communication using the internet network. The indicators of the perceived innovation that influence adoption are relative advantages (e-commerce has broad market access, and provides a system for sales, payment, delivery, communication, marketing, and promotion), compatibility (e-commerce supports business activities according to retailers' daily habits and norms), complexity (retailers can create and manage online stores, upload and manage product inventories, and process online transactions), trialability (retailers can learn customer profiles, requirements, policies, costs, and functions), observability (retailers can evaluate sales performance, costs, competition among retailers, reviews and ratings).